Analysis of Determinants of Employee Performance at PT Ezar Jaya Resources - Fauzi, Fachri Ali; Lubis, Yusniar; Lubis, Adelina (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the factors that determine employee performance at PT Ezar Jaya Resources. The factors studied include competence, work culture, and job satisfaction, both partially and simultaneously on employee performance. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that competence has a significant influence on employee performance. Employees with higher competencies tend to have better work productivity and are able to complete tasks efficiently. In addition, work culture also plays a role in shaping a conducive work environment, where employees who work in a positive culture are more motivated and show high loyalty to the company. Job satisfaction was also found to be an important factor that had an impact on employee enthusiasm and dedication at work. Employees who are satisfied with the compensation system, work environment, and career development opportunities show more optimal performance. Further analysis revealed that competence, work culture, and job satisfaction simultaneously had a greater influence on employee performance than if these factors were analyzed separately. Therefore, companies need to manage these three factors effectively to increase the productivity and competitiveness of companies in the plantation industry.